Tunes, Tubes and Clouds: Getting Your In-House Talent Out of the House and Online. Part 2: Distribution. (15th June 2016) - Bates, Daniel
Abstract: In this second of a series of two articles, Daniel Bates considers some of the most popular online platforms which are available to host and promote audio and video content for purposes including knowledge-sharing, teaching, research dissemination, and profile-building.